In Vitro Release Kinetics Study of Different Brands of Esomeprazole Sustained Release Tablets Available in Bangladesh (Stamford Journal of Pharmaceutical Sciences, 2010)
Commercially available four national and four international brands of esomeprazole magnesium sustained release matrix tablets were studied in simulated gastric medium (pH 1.2) for 2 hours and simulated intestinal medium (pH 6.8) for 8 hours time period using USP reference dissolution apparatus. All the national and international brands complied with the USP in-vitro dissolution specifications for drug release in simulated gastric medium. However, one of the national brands (Code: MP-1) and one of the international brands (MP-7) failed to fulfill the official requirement of 80% drug release within 8th hour in simulated intestinal medium. Drug release of that national and international brand were 70.49% and 67.05% respectively within the specified time period, however one national brand (Code: MP-4) released 103.46 % drug within 8th hour in intestinal medium. Drug release profiles were analyzed for zero order, first order and Higuchi equation to reveal the release kinetics perspective of esomeprazole magnesium sustained release matrix tablets. It was found that zero order release kinetics was the predominant release mechanism than first order and Higuchi release kinetics for those brands (Code: MP-2, MP-3, MP-4, MP-5, MP-6 and MP-8) which complied with the USP in vitro dissolution specification for drug releases. On the other hand, first order release kinetics was predominant for one national and also one international non compliant brands (Code: MP-1 and MP-6). Key Words: In vitro dissolution; Sustained release; Market preparations; Kinetic analysis; Esomeprazole; National brand; International brand. DOI: 10.3329/sjps.v2i1.5812Stamford Journal of Pharmaceutical Sciences Vol.2(1) 2009: 27-31